Effect of additives in semen extender on post thaw sperm quality and plasma membrane protein profile of boar semen - BAISHYA, S K; BISWAS, R K; KADIRVEL, G; THAKURIA, D R (The Indian Journal of Animal Sciences, 2015)
The objective of the study was to evaluate the effect of butylated hydroxytoluene (BHT), cholesterol-loaded methyl-ß-cyclodextrin (CLC), and their combination on sperm motility, viability, plasma membrane integrity and membrane protein profile of frozen-thawed boar semen. Ejaculates (16) from 6 boars were utilized. Each ejaculate was split into 4 fractions and cryopreserved in semen extender containing BHT (0.2 mM), CLC at 5 mg/ 200–240 × 106 sperm, BHT (0.2 mM) plus CLC at 5 mg/ 200–240 × 106 sperm or without BHT and CLC. Semen samples were evaluated for sperm motility, viability (propidium iodide assay), plasma membrane integrity (HOST) and membrane protein profile (SDS-PAGE) after equilibration and after freezing. The supplementation of BHT, CLC, and BHT plus CLC in semen extender significantly improved the viability and plasma membrane integrity after freezing as compared to control. Post thaw sperm motility was also significantly higher in BHT and BHT plus CLC. In addition, the number of sperm plasma membrane protein loss was less in additive treated sperm as compared to that in non-additive treated sperm. Among the additives, BHT plus CLC showed a significant improvement on post thaw sperm motility along with a non-significant improvement on other sperm parameters as compared to BHT and CLC alone. In conclusion, the supplementation of BHT, and CLC in extender before freezing improved the quality of cryopreserved boar semen and, the beneficial effect was more pronounced when BHT was combined with CLC than with BHT and CLC alone.